Executive function deficits mediate the relationship between employees' ADHD and job burnout - Yaara Turjeman-Levi; Guy Itzchakov; Batya Engel-Yeger (AIMS Press, 2024)
Adults with Attention-Deficit/Hyperactivity Disorder (ADHD) often face significant deficits in executive function and adverse work-related outcomes. This study aimed to explore the role of executive function deficits in job burnout of employees with ADHD. We hypothesized that employees with ADHD, relative to employees without ADHD, will experience higher levels of job burnout and deficits in executive function. We also hypothesized that the ADHD-job burnout relationship would be mediated through executive function deficits, specifically by self-management to time and self-organization/problem-solving. A field study with 171 employees provided support for the research hypotheses and mediation model in which the employees' ADHD-job burnout relationship was mediated through executive function deficits. Additional mediation analyses indicated that the specific executive function of self-management to time and self-organization/problem-solving mediated the effect of ADHD on job burnout and its facets. Specifically, for physical fatigue, the mediation was realized through self-management to time, and for emotional exhaustion and cognitive weariness, the mediation was significant through self-organization/problem-solving. The present findings shed light on the relevance of referring ADHD among employees, their vulnerability to job burnout, and the role of executive function deficits in job burnout of employees with ADHD.